High-index faceted Au nanocrystals with highly controllable optical properties and electro-catalytic activity - Rajendra, Ranguwar; Gangadharan, Pranav K.; Tripathi, Shalini; Kurungot, Sreekumar; Ballav, Nirmalya (Nanoscale, 2016)
We introduce a new and naturally abundant mild reducing agent, tannic acid, to improve the seed-mediated growth method for the synthesis of elongated tetrahexahedral Au nanocrystals enclosed with high-index (730) planes, at room-temperature. The control of the dimensions, plasmonics and electro-catalysis of such high-index faceted nanocrystals is remarkable.

Seed-mediated growth of Pt on high-index faceted Au nanocrystals: the ag lining and implications for electrocatalysis - Roy, Debashree; Rajendra, Ranguwar; Gangadharan, Pranav K.; Pandikassala, Ajmal; Kurungot, Sreekumar; Ballav, Nirmalya (ACS Applied Nano Materials, 2021)
Bimetallic Au@Pt nanocrystals (NCs) offer a unique combination of plasmonic and catalytic properties and are a growing field of research. Herein, we report an unusual observation in the behavior of silver ions (Ag+) which was found to play a dominant role in dictating the Pt deposition in a seed-mediated growth method. `While the literature is replete with various instances of Ag-assisted Pt deposition whereby higher concentration of Ag+ translates into a thicker Pt shell, in the present study, contradictory observations were made. In the presence of lower amounts of Ag+, thick Pt shells were visualized, while at higher concentrations of Ag+, the extent of Pt deposition via the galvanic replacement reaction was reduced. Additionally, the presence of Ag was deemed necessary for the Pt deposition to take place, either in the form of an underpotential deposition layer on the Au NCs or by introducing Ag+ in the growth solution. We have demonstrated our findings on two different Au NCs enclosed with high-index facets, concave cuboid, and elongated tetrahexahedra, which mirror similar observations and provide generality to our claim. To the best of our knowledge, the time required for Pt deposition on the Au core in the present work is the least among the reported seed-mediated routes. Furthermore, this work, besides presenting a facile and general route for the amalgamation of catalytic and plasmonic properties in hybrid Pt-Au NCs, sheds light on the mechanistic aspects of Ag-assisted wet-chemical generation of bimetallic Au@Pt NCs. The overall electrocatalytic performance of our Au@Pt NCs toward the oxygen reduction reaction was realized to be impressive.
Keywords: bimetallic nanostructure; galvanic replacement reaction; high-index facet; oxygen reduction reaction; seed-mediated growth; underpotential deposition